PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SUB BAGIAN TATA USAHA DI KANTOR KEMENTERIAN AGAMA KOTA PADANG - Erdianti, Novia; Hasnawati, Hasnawati; Sermal, Sermal (UIN Imam Bonjol Padang, 2024)
This research is motivated by the fact that employees' work motivation has not been measured so that it has an unfavorable impact on their performance. This research aims to find out what the level of employee work motivation is, what the level of employee performance is and whether there is an influence of Work Motivation on Employee Performance in the Administrative Sub division at the Padang City Ministry of Religion Office. The hypothesis proposed is whether there is an influence between work motivation and the performance of employees in the Administration Sub division at the Padang City Ministry of Religion office. In his research there are two variables, namely the independent variable (workmotivation) and the dependent variable (employee performance). This research is field research using a quantitative approach. This research method uses correlation with the Simple Linear RegressionTest (TTest). The population in this study was 31 employees taken using total sampling. The research instrument used 2 (two) questionnaires, Namely a questionnaire about Work Motivation and Employee Performance. Data were processed using (SPSS) Version 20. Research results:1) Work motivation is a the medium category level at 77% (24 employees); 2) Employee performance is also at the medium category level at 74% (23 employees); 3) There is a significant influence between work motivation and employee performance in the administration sub-section